Analysis Of Factors Related To Quality Of Health Services On Inpatient Satisfaction In North Sumatera Hospital: (A Systematic Review) - Riza Faradiba; Susilawati (International Archives of Medical Sciences and Public Health, 2022)
Background: a patient's satisfaction can be seen from the results of services provided by hospital health workers, patients are satisfied if their needs and complaints can be granted. The dimensions of the quality of health services become the reference point in measuring the good or bad quality of health services, which consist of physical evidence, responsiveness, reliability, assurance, and care from the hospital for patients. Objective: This study aims to determine the factors associated with the quality of health services on the satisfaction of inpatients at the North Sumatra Hospital. Methods: This research uses a literature review study using the PRISMA model and database searches through Google Schoolar and Garuda. Results: Of the 9 journals studied in the literature, it was found that on average they have dimensions of health service quality in the good category, but some aspects need to be further improved in order to make the quality of hospital services even better. Conclusion: it is known from the identified journals that hospitals in North Sumatra have a close relationship with the dimensions of the quality of health services.